2015
DOI: 10.5152/eajem.2015.71354
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Pediatric Psychiatric Emergency Population in a Mental Health Hospital

Abstract: Aim: We aimed to investigate the characteristics of children and adolescents presented to the psychiatric emergency service (PES) of a mental health hospital. Materials and Methods:Medical records of patients under 18 years of age were reviewed for the first psychiatric emergency visit during a 1-year period. Results:The mean age was 15.82 years and 65.8% (n=711) were female. The most presenting symptoms were suicidal ideation (21.0%; most for girls) and homicide/violence toward others (20.7%; most for boys). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
3
3
0
Order By: Relevance
“…15 Mutlu et al conducted a study revealing that the predominant symptoms leading to admissions to the psychiatry emergency department over a one-year period were suicidal ideation (21.0%) and aggression (20.7%). 25 Our study findings are consistent with the existing literature regarding the reasons for requesting consultations. Furthermore, given that psychosomatic symptoms emerged as the third most common reason for consultation in our sample, it underlines the importance of employing comprehensive psychiatric evaluation and treatment approaches.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…15 Mutlu et al conducted a study revealing that the predominant symptoms leading to admissions to the psychiatry emergency department over a one-year period were suicidal ideation (21.0%) and aggression (20.7%). 25 Our study findings are consistent with the existing literature regarding the reasons for requesting consultations. Furthermore, given that psychosomatic symptoms emerged as the third most common reason for consultation in our sample, it underlines the importance of employing comprehensive psychiatric evaluation and treatment approaches.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, agitation can also occur in medical conditions unrelated to psychiatric disorders, such as delirium, traumatic brain injury, infections, and adverse effects of medications. 25 Since agitation is a symptom covering many conditions, it may have appeared as a factor predicting the follow-up. At the same time, the outward and sometimes destructive nature of such symptoms leads the person or the physician to seek assistance and intervention.…”
Section: Discussionmentioning
confidence: 99%
“…As far as clinical features of these patients are concerned, this study reveals that in each considered year, the most frequent diagnosis reported in medical records is conduct disorders, mainly registered in male, but also in female, both in Italians and foreigners, whether voluntary admitted or not. This result is consistent with Finnish, Turkish, and German research that consider minors in psychiatric emergency setting [ 12 , 13 , 15 ]. In addition, this study points out that comorbidity is often associated with admission age older than the average (17 years) because during the process of growing up the onset of a new psychiatric condition in people already affected by another one is not rare, which can be both cause and consequence of the previous mental health status and share with the latter the same biologic and environmental background.…”
Section: Discussionsupporting
confidence: 91%
“…Results show that minor inpatients' mean age is 15.7 years, which is consistent with several studies carried out in other countries such as Turkey, where in a sample of 1080 patients, the mean age was 15.8 years [ 12 ], and Finland, where a mean age of 15.1 and 15.9 years was found in two different hospital districts [ 13 ]. This indicates that the process of growing up, from childhood to adulthood, is a period of weakness for the mental health status.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation